COLLABORATION BETWEEN PARENTS AND HOMEROOM TEACHER IN INCREASING THE LEARNING MOTIVATION OF FIFTH GRADE STUDENT IN MI MATHLAUL ANWAR TALANG PADANG DURING THE COVID-19 PANDEMIC: indonesia - Dwi Rohmadi Mustofa; Ahmad Zaenuri; Feri Wahyudi (STIT Pringsewu, 2021)
Abstrack In general this study aim to determine the cooperation of parents and homeroom teacher in increasing the learning motivation of grade V students at the MI Mathlaul Anwar Talang Padang during the covid-19 pandemic. The data were analyzed by means of a qualitative descriptive analysis. Data collection using interview teachniques, observation and documentasi. This research is to see the problems that occur in these madrasas. This is beause there is still a lack of cooperation between parents and homeroom teachers in increasing student motivation. Students are still less active in learning in lack of student motivation in the learning process so that student learning is still low. Keywords: Collbaration, Motivation